ANALYSIS OF CASH FLOW STATEMENTS TO ASSESS FINANCIAL PERFORMANCE IN TELECOMMUNICATIONS COMPANIES ON THE INDONESIA STOCK EXCHANGE - Qhisthina Atikah; Ade Dhitta Vianda; Ratna Sari Siregar; Abdur Rasyid Zasri; Ulya Liana (RADJA PUBLIKA, 2023)
Companies must observe and analyze company performance in order to survive, one of which is by analyzing financial performance from the financial side of the financial statements. One way to measure a company's performance level is to use a cash flow statement. Research on the performance of a company can be done by analyzing two aspects, namely financial performance and non-financial performance. Financial performance can be seen through financial report data. This study aims to determine the financial performance of telecommunications companies using cash flow statements. The analytical method used in this research is descriptive qualitative. The results of this study state that the average with the highest turnover rate from the results of the calculation of all cash flow statement ratios is PT. Telekomunikasi Indonesia Tbk (TLKM), where this can be seen from all the results of the calculation of the ratio of cash flow statements which are shown through the turnover results and percentages from PT. Telekomunikasi Indonesia Tbk (TLKM). Improving the company improves company performance by reducing the amount of debt and increasing operating cash flow.